Case Report: A Man (47 Years Old) With Vivax Malaria, Hypotension, Anemia, Thrombocytopenia, Hypokalemia And Renal Insufficiency - Karina Agusta Putri; Indria Augustina (The International Journal of Medical Science and Health Research, 2025)
Vivax malaria is an infectious disease caused by the Plasmodium vivax parasite that lives and reproduces in human blood cells and is transmitted through the bite of a female Anopheles mosquito. Malaria can reduce work productivity. In 2022, malaria in Indonesia was highest in the regions of East Kalimantan, East Nusa Tenggara, and Papua. Central Kalimantan itself is categorized as having mild-to-moderate endemicity. There were 47 cases of malaria in the Murung Raya region, Central Kalimantan in 2023. The typical clinical manifestation of malaria fever is the malaria triad. Diagnosis is made by finding the plasmodium on microscopic examination. A 47-year-old man presented with a 10-day fever; the fever was intermittent, accompanied by complaints of chills followed by cold sweats, weakness, and headache. On physical examination, decreased blood pressure and reduced motor status were found. Laboratory examinations revealed normocytic normochromic anemia, thrombocytopenia, hypokalemia, and increased creatinine; a microscopic blood smear was positive for Plasmodium vivax. The patient was diagnosed with vivax malaria. Pharmacological therapy consisted of antimalarials (a combination of dihydroartemisinin for three days and primaquine for fourteen days). Management was adjusted according to the malaria management guidelines issued by the Ministry of Health of the Republic of Indonesia.